The Influence Of Work Ethic On Employee Performance Through The Work Motivation Of YPK Merauke High School Employees - Asna, Maria; Yustiana, Dewi; Endriatmoko, Yosa; Handayani, Sari; Nafisah, A'isy Fiklil (Abadi Institute, 2025)
This study aims to analyze the influence of work ethic on employee performance, either directly or through work motivation as a mediating variable at SMA YPK Merauke. Employee performance is an important factor in achieving quality education, so it needs to be improved through strengthening work ethic and motivation. Work ethic is understood as a positive attitude and responsibility towards work, while work motivation refers to internal and external drives that affect an individual's work ethic. This study uses a quantitative approach with a population of 105 employees, and the sampling technique is carried out in saturated samples. The data analysis technique used is Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of the study show that work ethic has a positive and significant effect on employee performance, both directly and indirectly through work motivation. Work motivation has been proven to be a mediating variable that strengthens the relationship between work ethic and employee performance. These findings provide practical implications for school management to improve employee performance through the development of a work ethic and effective work motivation.